2003
DOI: 10.1128/jvi.77.2.1281-1291.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Tail of Moloney Murine Leukemia Virus Envelope Protein Influences the Conformation of the Extracellular Domain: Implications for Mechanism of Action of the R Peptide

Abstract: The envelope (Env) protein of Moloney murine leukemia virus (MoMuLV) is a homotrimeric complex whose monomers consist of linked surface (SU) and transmembrane (TM) proteins cleaved from a precursor protein by a cellular protease. In addition, a significant fraction of virion-associated TM is further processed by the viral protease to remove the C-terminal 16 amino acids of the cytoplasmic domain, the R peptide. This cleavage greatly enhances the fusogenicity of the protein and is necessary for the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 81 publications
2
60
0
1
Order By: Relevance
“…The structural alteration in the Env endodomain seems also to transmit changes into the ectodomain. Although in our structure reconstructions we were unable to find significant differences between the ectodomains of the precursor and the mature Env, biochemical mapping using antibodies and biotinylation have shown that the R-peptide cleavage is associated with ectodomain changes (20).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The structural alteration in the Env endodomain seems also to transmit changes into the ectodomain. Although in our structure reconstructions we were unable to find significant differences between the ectodomains of the precursor and the mature Env, biochemical mapping using antibodies and biotinylation have shown that the R-peptide cleavage is associated with ectodomain changes (20).…”
Section: Discussionmentioning
confidence: 83%
“…This has been suggested to inhibit the receptor triggering of the R-peptide Env precursor. The model was tested by analyzing the fusion phenotype of an Env with a mutation of Leu651 into Ala (19,20). Leu651 is positioned just behind the Leu649/Val650 cleavage site and is predicted to be one key residue in the heptad repeat of hydrophobic residues specifying the trimeric coiled-coil structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many examples in the literature describe the cytoplasmic domain as important for the function of the ectodomains of glycoproteins in a variety of virus families [16][17][18][19][20]. Studies examining conformation dependent binding of monoclonal antibodies showed that alterations in the cytoplasmic domain led to structural changes in the ectodomain [21,22]. Moreover, our data highlight that the cytoplasmic domain is an important factor for a correct quaternary structure, which subsequently is required for proper proteolytic processing and function of the viral glycoprotein.…”
Section: The Cytoplasmic Domain Stabilizes Non-cleaved Gp-c For Maturmentioning
confidence: 99%
“…For the paramyxovirus SV5 F protein, isolates with a short (20-residue) CT (W3A and WR) cause extensive cell-cell fusion, whereas isolates with an extended CT (T1 and SER) cause little or no cell-cell fusion, and truncation of the CT restores fusion to levels seen in W3A and WR isolates (28,65). For MoMuLV, SIV, and SV5, the hyperfusogenicity caused by truncation of the CT is linked to overall conformational changes in the ectodomain of the protein (2,61,67). In MoMuLV and the Mason-Pfizer monkey virus, the CT is even protease cleaved during viral maturation to "prime" the fusion protein for fusogenicity (2,13).…”
mentioning
confidence: 99%